KASIH IBU (Edukasi Mengenai ASI Eksklusif dan MP-ASI Pada Ibu) At Posyandu Kenanga 1, Cipadu Village, Larangan District, Tangerang City : Program KASIH IBU (Edukasi Mengenai ASI Eksklusif dan MP-ASI Pada Ibu) Di Posyandu Kenanga 1, Kelurahan Cipadu, Kecamatan Larangan, Kota Tangerang - Anwar, Khoirul; Nanda, Elza; Permana, Juwita Cahaya; Sulistyaningsih, Lilis; Fitri, Yuni Pradilla; Maskar, Dadi H (Poltekkes Kemenkes Palu, 2023)
Wasting is one of the malnutrition that occurs in children and is a nutritional problem that is currently still occurring in Indonesia with the prevalence of wasting in Indonesia in 2021 namely 7.1% while in Tangerang City it is 5.9% in 2021. The purpose of the implementation of this program is to increase the knowledge of pregnant and lactating mothers at Posyandu Kenanga 1, Cipadu Village, Larangan District, Tangerang City regarding exclusive breastfeeding and complementary feeding. The method used in the implementation of this program is counseling and cooking demonstrations using leaflet as a media through 3 stages, namely the stages of preparation, implementation, and evaluation. Based on the implementation of the